Efficacy analysis of modified halo-pelvic traction combined with pedicle subtraction osteotomy for severe adolescent idiopathic scoliosis - Li, Li; Xu, Zhu; Yuan, Ma (Frontiers in Surgery, 2026)
BackgroundTreatment of severe adolescent idiopathic scoliosis (AIS) is challenging, and traditional halo-pelvic traction (HPT) presents multiple disadvantages. This study evaluated the efficacy of modified HPT combined with Pedicle Subtraction Osteotomy (PSO).MethodsA retrospective analysis was performed on 38 patients with severe AIS treated from January 2023 to May 2024. Sixteen patients (modified group) received modified HPT combined with PSO, and 22 patients (control group) underwent traditional HPT combined with PSO. Correction efficacy, pulmonary function, and complications were compared between groups.ResultsThere were no significant differences between the two groups regarding baseline characteristics before treatment (P > 0.05). The correction rate of deformity after traction in the modified group was significantly higher than in the control group (P = 0.003 in the sagittal plane), and the improvement in FEV1 and FEV1% after traction was also significantly greater (P < 0.05). No significant differences in surgical parameters were observed between the two groups. The total complication rate in the modified group (6.3%) was lower than in the control group (9.1%). At one-year follow-up, Cobb angles in the coronal and sagittal planes were maintained at 45.94 ± 2.91 ° and 45.06 ± 1.88 °, respectively, with an average height increase of 9.38 ± 0.72 cm in the modified group.ConclusionBoth modified and traditional HPT combined with PSO are effective and safe. The modified technique may offer additional advantages in sagittal plane correction and pulmonary function improvement, representing a viable alternative treatment for severe AIS. Further studies with larger sample sizes are warranted to validate these potential benefits.